Nursing care to the newborn under phototherapy: students’ view in the practice field - Antônia do Carmo Soares Campos; Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
We aimed at comparing the theoretical content taught in classroom with the students’ practice in the care to the newborn under phototherapy and at evaluating the students’ involvement in the care to the newborn under phototherapy in their first experience of hospital practice. The study was conducted from October to December/2003 in a public institution in Fortaleza-CE, with undergraduate students at the 4th semester taking ‘Nursing in the Care Process I (child and adolescent)’ at Universidade Federal do Ceará. The methodology consisted of a theoretical class focusing on the theme ‘Phototherapy and the nursing care to the newborn’, and experience in the practice field. We used as strategies dialogued exposition, teamwork activities and a questionnaire contemplating the objectives proposed. The results revealed that there is a correlation between theory and practice; the student is moved by the fragility of the newborn under phototherapy and the methodology has been viable, contributing to the criticalreflective doing of the students considering the human being as the center of convergence of nursing humanized care.